Genetic variability, character association and path coefficient analysis in China aster (Callistephus chinensis) - RAI, TEERATH SINGH; CHAUDHARY, S V S; DHIMAN, S R; DOGRA, R K; GUPTA, R K (The Indian Journal of Agricultural Sciences, 2017)
Ten cultivars of China aster [Callistephus chinensis (L.) Nees] were evaluated for 12 growth and flowering related traits to study their genetic parameters such as variability, heritability, genetic coefficient of variation (GCV), phenotypic coefficient of variation (PCV), correlation and path coefficient analysis. Significant differences among cultivars for all the growth and flowering related traits were reported through analysis of variance. Wide range in mean performance has been reported in characters such as plant height (41.15-102.25 cm), plant spread (23.79-55.70 cm), days to first flower opening (77.25-106.25 days), flowering duration (25.65-41.30 days) and weight of flowers/plant (84.50-174.42 g). Higher genotypic and phenotypic coefficient of variation was recorded for plant height and plant spread. High heritability (>80%) was recorded for all traits, except number of harvests of loose flower. The genetic advance ranged from 1.36 (individual flower weight) to 57.15 (weight of flowers/plant). High values of genetic gain were recorded for plant height (69.81%), followed by weight of flowers/plant (50.97%). Weight of flowers/plant is significantly and positively correlated both at genotypic and phenotypic level to plant height, plant spread, flower head diameter, number of flowers/plant and individual flower weight. Path coefficient analysis using correlation coefficients revealed that number of flowers/plant contributed highest positive direct effect on weight of flowers/plant, followed by individual flower weight and plant height. Various cultivars performed differently for various quantitative characters. Therefore, cultivars with superior traits can be utilised in hybridization to transfer desirable traits into a single cultivar.